2017
DOI: 10.3390/rs9070743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the U.S. Geological Survey Landsat Burned Area Essential Climate Variable across the Conterminous U.S. Using Commercial High-Resolution Imagery

Abstract: The U.S. Geological Survey has produced the Landsat Burned Area Essential Climate Variable (BAECV) product for the conterminous United States (CONUS), which provides wall-to-wall annual maps of burned area at 30 m resolution . Validation is a critical component in the generation of such remotely sensed products. Previous efforts to validate the BAECV relied on a reference dataset derived from Landsat, which was effective in evaluating the product across its timespan but did not allow for consideration of inacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…It was found that, for the standard NASA BA product [8], derived from the MODIS sensor, the BA omission error was above 65% (at a global scale) [9]. Using sensors, such as Landsat or Sentinel-2, with higher spatial resolution (20-30m instead of 500m), but worse temporal resolution (5-16 days instead of 1-2 days), the performances improved and omission errors equal to around 40% [10,11], 26.5% [12], and 22% [13] were obtained (generally, at smaller spatial scales).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that, for the standard NASA BA product [8], derived from the MODIS sensor, the BA omission error was above 65% (at a global scale) [9]. Using sensors, such as Landsat or Sentinel-2, with higher spatial resolution (20-30m instead of 500m), but worse temporal resolution (5-16 days instead of 1-2 days), the performances improved and omission errors equal to around 40% [10,11], 26.5% [12], and 22% [13] were obtained (generally, at smaller spatial scales).…”
Section: Introductionmentioning
confidence: 97%
“…Undetected clouds represent the major source of commission errors; it was found that commission error was above 40% (at a global scale) for the standard NASA BA product [8] , while it ranged between 48% and 19% for operational BA products derived from higher resolution sensors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The Landsat Burned Area Essential Climate Variable (BAECV) product is a 30 m resolution burned area product over the conterminous United States (CONUS) generated by the U.S. Geological Survey. Vanderhoof et al [14] assessed the BAECV with burned area reference maps derived from high-resolution satellite images. A maximum likelihood supervised classifier trained with manually created burned data was used to generate the reference maps.…”
Section: Product Validationmentioning
confidence: 99%
“…Cropland land cover was not considered in our analysis, since the MODIS burned area product is not suited to capturing the size and heterogeneity of cropland burned areas [18,99] because of its geometrical resolution, and because other agricultural practices (e.g., tilling) often immediately follow the fires [100], and have similar spectral signatures [101]. Omission errors in the cropland class of the MCD12Q1 land cover product, therefore, led to the inclusion of MCD64A1 detections over agricultural areas in the burned population ba.…”
Section: Ecoregion-level Burned Area Persistence Timementioning
confidence: 99%